2017
DOI: 10.17511/ijpr.2017.i10.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dengue fever on the total leucocyte count and neutrophil count in children in early febrile period

Abstract: Introduction: Dengue is an arboviral disease caused by flavivirus. In India, the incidence of dengue fever is on a rise every year. The course of illness is different for each patient. Therefore early measurement of laboratory parameters can guide to the management of the disease. Aim of the study: 1) To study the effect of dengue fever on the total leucocytecount (TLC) in children in early febrile period. 2) To determine the neutrophil count in early stage of dengue fever. Study design: Observational study. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
1
2
0
2
Order By: Relevance
“…Ralapanawa et al reported 70.9% of the patients had WBC count of <50000 in dengue fever 27 . On the contrary, leucopenia was observed in only 32% of the patients in our study, which was supported by the study of Khandelwal and colleague that the majority of the patients had WBC count within the normal range during the early febrile period of the disease and change in leukocyte count show progression towards severe disease 28 .…”
Section: Discussionsupporting
confidence: 87%
“…Ralapanawa et al reported 70.9% of the patients had WBC count of <50000 in dengue fever 27 . On the contrary, leucopenia was observed in only 32% of the patients in our study, which was supported by the study of Khandelwal and colleague that the majority of the patients had WBC count within the normal range during the early febrile period of the disease and change in leukocyte count show progression towards severe disease 28 .…”
Section: Discussionsupporting
confidence: 87%
“…Hallmark features of human DHF/DSS are vascular leakage, greater viral burdens, elevated serum cytokine levels, hypotension, and thrombocytopenia (27,28). Although leukopenia is a common feature found in patients with DENV infections, normal white blood cell counts or leukocytosis may also occur during DENV infections, as observed in experimental models (19,20) and in children (30). Here we showed that compound 10 delivered as a preventative (day 0) or therapeutic (day 2 postinfection) modality prevented loss of body weight, mitigated viral induction of inflammation, ameliorated leukocytosis induced by infection, especially by reduction of circulating neutrophil levels, and protected against hepatic edema.…”
Section: Zandi Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 99%
“…The total leucocyte count was significantly low in dengue without warning signs and severe dengue compared to dengue with warning signs. The change in total leucocyte count predicts the progression of dengue, as reported by Khandelwal and Khandelwal [16]. No correlation was seen between leucopenia and the severity of dengue and its complications by Jayanthi and Tulasi [17].…”
Section: Discussionmentioning
confidence: 78%